Communication and Mathematic reasoning: Theory of planned behavior and inquiry - Abdul Aziz; Iswahyudi Joko Suprayitno (Journal of Educational Management and Instruction (JEMIN), 2021)
The purpose of this study is to investigate the aspects of communication and mathematical reasoning. In investigating the aspects of mathematical communication with an inquiry approach, of course there are several things observed related to learning mathematics. The focus of the material aims at observing communication and mathematical reasoning within the framework of inquiry, and the theory of planned behavior (TPB) is geometry and algebra. The research method used a qualitative research by looking at case studies with research subjects consisting of 31 prospective mathematics teachers in Semarang city. From the aspect of communication and mathematical reasoning that exists, it can be seen from the answers of 31 prospective mathematics teachers with an authentic point of view of inquiry and a theory of planned behavior for problem solving. From the observation, several cognitive processes are adapted to the authentic framework of inquiry and the theory of planned behavior for algebra and geometry material. In reasoning, a wedge appears between mathematical reasoning and communication adapted to the framework of inquiry and the theory of planned behavior. The contribution of this study is to determine the communication framework and mathematical reasoning from the theoretical aspects of planned behavior and inquiry. It is important to know aspects of communication and mathematical reasoning from a different perspective.